Gestational Age-Specific Distribution of the Hammersmith Neonatal Neurological Examination Scores Among Low-Risk Neonates in Ghana. (January 2021) - Lawford, Harriet L.S.; Nuamah, Mercy A.; Liley, Helen G.; Lee, Anne CC; Botchway, Felix; Kumar, Sailesh; Adjei, Andrew A.; Bora, Samudragupta; ,
Abstract: Objective: To describe gestational age-specific distribution of scores for the Hammersmith Neonatal Neurological Examination (HNNE) up to 48 h after birth in a low-risk, term-born, single-center sample in Ghana. Study design: This is a nested substudy of a larger prospective study (IMPRINT: Impact of Malaria in Pregnancy on Infant Neurodevelopment) comprising 140 low-risk, term-born neonates at Korle Bu Teaching Hospital in Accra, Ghana, between November 2018 and February 2019. The sample was stratified into three gestational age groups: early-term (37 + 0–38 + 6,  weeks + days; n  = 61), full-term (39 + 0–40 + 6,  weeks + days; n  = 52), and late/post-term (41 + 0–42 + 6,  weeks + days; n  = 27). Neonates were administered the 34-item HNNE by trained physicians. As per the original British scoring system, raw scores for the Ghanaian sample were plotted and scores > 10th centile were assigned a score of 1, 5th–10th centile 0.5, and < 5th centile 0. Results: The range of raw scores for 16/34 HNNE items varied with gestational age. Specifically, 100% (7/7), 50% (5/10), 33% (1/3), 33% (1/3), 20% (1/5), and 14% (1/7) of items within the orientation and behavior, tone, abnormal signs/patterns, movements, tone patterns, and reflexes subdomain, respectively showed a different distribution of scores above the 10th centile across the three gestational age groups. Conclusion: Differences in gestational age-specific results within our sample in comparison to the original British sample could be, albeit unlikely, due to misclassification of gestational age, unmeasured maternal or fetal morbidity, or perhaps more likely, variation in testing or test conditions, or some combination of these. Genetic variation in neurological development is also a possibility. Further research is warranted to determine the reasons for differences. Our findings highlight the need to determine the accuracy and reliability of standardized neurologic assessments in predicting neurodevelopmental risk for infants in low- and middle-income countries. Highlights: Gestational age-specific distributions of HNNE scores of Ghanaian infants are shown. Overall, 16/34 items varied with gestational age in Ghanaian infants. Further research is warranted to determine the reasons for these differences. Our results may aid studies determining the predictive value of the HNNE in Ghana